Synergistic Action of Alginate Chemical Reduction and Laser Irradiation for the Formation of Au Nanoparticles with Controlled Dimensions. (22nd September 2014) - Anyfantis, George C.; Scotto, Marco; Scarpellini, Alice; Pignatelli, Francesca; Toussi, Setareh M.; Ruffilli, Roberta; Martiradonna, Luigi; Athanassiou, Athanassia
<x xml:space="preserve">Abstract</x> Freestanding natural polymeric films with homogeneous dispersion of gold nanoparticles (Au NPs) are obtained via in situ reduction of gold(III) chloride trihydrate by sodium alginate (SA) biopolymer matrix, during water evaporation without the use of additional reducing agents. The size and size distribution of the prepared Au NPs can be tuned by changing the concentration of the precursor and/or the procedure of the films' preparation. The nanocomposite films after preparation are stable in ambient conditions and can be used without the need of further processing, or can be redissolved in water. In the case of water dissolution, the aqueous solutions are irradiated with UV laser pulses turning the previously formed Au NPs into smaller ones with narrow size distributions through photofragmentation. This technique is proposed as a green way of synthesizing Au NPs of tunable size in aqueous solution of alginate, or incorporated in alginate freestanding polymeric films, that due to their biocompatibility can be used as passive labels or active sensors in biomedical applications.